Optimalisasi Pengetahuan Ibu dalam Upaya Pencegahan dan Deteksi Dini Kanker Serviks di Posyandu Candra Sebawi - FANIA, UMI; Oktavianty, Merry (LOSARI DIGITAL, 2025)
Cervical cancer is one of the leading causes of death among women, ranking second after breast cancer, making it very important to anticipate factors that may influence the occurrence of this condition as early as possible. Early detection of cervical cancer is clearly dependent on women's knowledge of how to prevent it as early as possible so that the issue can be anticipated. The objective of this activity is to enhance the knowledge of women of childbearing age regarding prevention efforts and early detection of cervical cancer at UPT Puskesmas Sebawi. The method used for this community service involved conducting a pre-test, counseling, and a post-test. The evaluation results showed an increase in knowledge among women of childbearing age by 30.1%, and the Wilcoxon test analysis yielded a significance level of 0.000 (sign < 0.05).